2015
DOI: 10.1007/s12576-015-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentric contraction on satellite cell activation in human vastus lateralis muscle

Abstract: We compared the time-course of satellite cell (SC) activation between eccentric and concentric contractions in the vastus lateralis (VL) muscle after step exercise. Young adults participated in a 30-min step up/down exercise which mainly involved concentric contractions with the right VL muscle and eccentric contractions with the left VL muscle. The concentric and eccentric contraction phases of the VL muscles were identified by changes in the electromyogram (EMG) and knee joint angle. Biopsy samples were take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In fact, previous studies have shown a greater muscle damage in VI when compared to other vastii muscles after eccentric exercise using magnetic resonance imaging in human subjects . It should be noted that many of the studies in which histological changes induced by eccentric knee extensor exercise were investigated, muscle biopsy samples were obtained from VL only . It is possible that histological changes observed in VL underestimated global muscle damage.…”
Section: Perspectivementioning
confidence: 98%
“…In fact, previous studies have shown a greater muscle damage in VI when compared to other vastii muscles after eccentric exercise using magnetic resonance imaging in human subjects . It should be noted that many of the studies in which histological changes induced by eccentric knee extensor exercise were investigated, muscle biopsy samples were obtained from VL only . It is possible that histological changes observed in VL underestimated global muscle damage.…”
Section: Perspectivementioning
confidence: 98%
“…The number of satellite cells in disused muscle is known to be reduced, caused by impaired proliferation (Zammit et al 2006;Li et al 2016). The mechanical stretch causes satellite cell activation (Imaoka et al 2015). In this study, the satellite cells from disused muscle retained both their original proportions and myogenic potential as much as that from the intact muscle.…”
Section: Discussionmentioning
confidence: 53%
“…As stated above, TRPC1 likely plays an important role in satellite cell activation. Consistent with this, TRPC1 expression was significantly increased in satellite cells of the left VL muscle, suggesting that eccentric but not concentric exercise activates satellite cells in a TRPC1-dependent manner [21].…”
Section: Trpc1mentioning
confidence: 63%
“…As a signal mediator, Ca 2+ also plays a critical role in the activation of Nox proteins. Increased activity of TRPC channels has been reported in skeletal muscle after physical activity [21, 66]. In skeletal muscle, acute exercise increases Nox2 protein activity.…”
Section: Perspectivementioning
confidence: 99%